HBR's 10 must reads for mid-level managers. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"Collaborator. Communicator. Creator. Coach. Conduit. The pandemic, and the resultant ever-evolving landscape of hybrid work, highlighted that we're asking more of our mid-level managers than ever. You balance leading your team with maintaining your high-level individual performance. You provide feedback and coaching, support your people through tough times, field requests large and small, and communicate in every direction. Mid-level managers are the key to managing a hybrid workforce, leading innovation, managing talent, and helping your organization-and its people-adapt to our changing world. If you read nothing else on being an effective mid-level manager, read these 10 articles by experts in the field. We've combed through hundreds of Harvard Business Review articles and selected the best ones to help you manage up and down, interpret and distill important messages, lobby for time and resources for key projects and players, and lead change-all while getting things done. This book will inspire you to build teams and develop talent; transform your role from intermediary to innovator; encourage critical thinking; foster a culture of psychological safety; lead change by leveraging internal networks; understand the cognitive and emotional drain of having both high and low power; and form partnerships at every level of the organization"--
Managers Can't Do It All / by Diane Gherson and Lynda Gratton -- The Real Value of Middle Managers / by Zahira Jaser -- In Praise of Middle Managers / by Quy Huy -- Managing Your Boss / by John J. Gabarro and John P. Kotter -- Get the Boss to Buy In / by Susan (Sue) Ashford and James R. Detert -- The Secrets of Great Teamwork / by Martine Haas and Mark Mortensen -- How the Best Bosses Interrupt Bias on Their Teams / by Joan C. Williams and Sky Mihaylo -- Making the Hybrid Workplace Fair / by Mark Mortensen and Martine Haas -- Why Strategy Execution Unravels-and What to Do About It / by Donald Sull, Rebecca Homkes, and Charles Sull -- The Leader as Coach / by Herminia Ibarra and Anne Scoular -- Make the Most of Your One-on-One Meetings / by Steven G. Rogelberg -- Learn When to Say No / by Bruce Tulgan -- Begin with Trust / by Frances X. Frei and Anne Morriss.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Middle managers; Industrial management; Success in business; Cadres moyens; Gestion d'entreprise.; Succès dans les affaires; Industrial management; Middle managers; Success in business